Analysis of extra-cranial germ cell tumors in male children: Experience from a single centre in India - Hemanth Kumar; S.V. Saju; Venkatraman Radhakrishnan; Anand Raja; Trivadi S. Ganesan; Manikandan Dhanushkodi; Jayachandran Perumal Kalaiarasi; Nikita Mehra; Archit Joshi; Arun Kumar Rajan; Gangothri Selvarajan; Tenali Gnana Sagar (Elsevier, 2020)
Background: Extra-cranial germ cell tumors (GCT) are rare malignancies in children. There is paucity of data on presentation and outcomes of extra-cranial GCT in male children from India. Methods: The study included all extra-cranial GCT in male children <18 years of age treated at our centre from January 2000 to December 2018. Baseline demographics, clinical manifestations, pathology, treatment details and outcomes of these patients were analysed retrospectively from the case records. Results: The study included 35 male children with extracranial GCT. Of these, 28 patients had testicular GCT, 1 had retroperitoneal nodal GCT, 1 had paraspinal mass diagnosed as GCT, 1 had mediastinal GCT and 4 had sacrococcygeal teratoma. Mixed germ cell tumor was the commonest histological subtype. 16/28 (57.1%) patients with testicular GCT were diagnosed with stage IV disease. PEb (Cisplatin, etoposide, bleomycin) chemotherapy was the most common regimen administered. Among the patients with testicular GCT, the 4 year event free survival (EFS) was 73.3% and the overall survival (OS) was 87.9%. In Children's Oncology Group (COG) system of stages I, II and III, the 4 year OS was 100% and in stage IV it was 78.8%. Conclusion: Germ cell tumors of the testis are the most common extracranial GCT in childhood. Despite presentation in advanced stages, the majority can be cured with platinum based chemotherapy.